Unclad plastic optical fiber temperature sensor with a balloon-like structure - Sulaiman, Nazrah Ilyana (2022)
An unclad plastic optical fiber (POF) temperature sensor with high sensitivity is experimentally demonstrated in this work. The working principle of this developed unclad POF sensor is based on intensity-modulated technique. In general, position and length of the unclad region in this developed sensor has influenced the output light intensity, thus, influencing the sensor performance. In this work, we fixed the location of the unclad region at the middle of the sensor head. As for the length of the unclad region, optical intensity measurement was carried out. It was observed that the increment of length in the unclad region contributed to the increase of intensity losses. Therefore, the unclad length of 1.0 cm was considered as the optimal value due to its higher linearity and optical loss performances and was used in the bending analysis for balloon-like bent POF sensor. The sensor was realized by combining macro bending and the unclad region in the fabrication of its sensor head. The POF sensor was bent to a balloon-like structure to introduce the effect of macro bending. For optimization of the sensor performances, the sensor bending radius was varied. Experimental results suggest that performances of the POF sensor are optimized when the bending radius is fixed at 55 mm. With this amount of bending radius, temperature sensitivity up to 22.2 x10-3 °C -1 was achieved in the range from 40 °C to 80 °C with the linearity of 0.99 and resolution of 0.45 °C. This technique improves the POF temperature sensitivity in comparison to previous developments.